Educational Milk Processing for Community-Based Educational Tourism in Babadan Village - Anis Khoirin Hayati; Ali Adi; Anissa Alifia Imaniah; Mas Aldrin Zagna Rania Kartika; Muhammad Athallah Hazel Ornando; Yunita Wulandari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Milk is a nutritious commodity with high susceptibility to microbial contamination if improperly processed. Specific Background Babadan Village possesses strong dairy farming potential, yet community understanding of hygienic processing and product diversification remains limited, constraining economic value and educational tourism opportunities. Knowledge Gap Previous community practices focused mainly on raw milk production with minimal educational integration and product innovation for tourism purposes. Aim This study aimed to develop community knowledge and skills in safe milk processing and flavored milk production as a basis for educational tourism activities. Results The program, implemented through coordination, observation, and hands-on education involving local elementary students and residents, demonstrated improved understanding of pasteurization, sterilization, and product diversification, alongside increased community interest in educational tourism. Novelty This work integrates dairy processing education with tourism-oriented learning experiences for school-aged participants in a rural setting. Implications The findings indicate that educational milk processing activities can support local economic initiatives, strengthen community learning, and position villages as destinations for educational tourism.